Anatomical traits and economic potential of Amorphophallus variabilis and conservation implications in Selo Arjuno Forest, Central Java, Indonesia - BAIQ FARHATUL WAHIDAH; RIZKIATI KHASANAH; FADLY HUSAIN (Society for Indonesian Biodiversity, 2026)
Abstract. Wahidah BF, Khasanah R, Husain F. 2026. Anatomical traits and economic potential of Amorphophallus variabilis and conservation implications in Selo Arjuno Forest, Central Java, Indonesia. Biodiversitas 27 (2): d270213. https://doi.org/10.13057/biodiv/d270213. Amorphophallus variabilis is rarely utilized or studied despite its ecological and economic value. This study aimed to identify its anatomical characteristics, secretory structure, and the distribution of ergastic substances in its organs, including assessing their implications for conservation and local economic development. The study was conducted in Selo Arjuno Forest, Kendal District, Central Java, Indonesia. Anatomical slides from six mature individuals were prepared with paraffin methods and examined under a light microscope. Socio-economic data were collected through in-depth interviews. All data were analysed descriptively. The results showed that tubers are the primary storage organs, with a very high starch granule content (±8400/mm²), far exceeding those in petioles (±25/mm²) and leaf blades (±71/mm²). Sand and druse calcium oxalate crystals dominate tubers, contributing to stress tolerance. Tannin distribution is organ-specific, namely schizogenous cavities are more abundant in petioles, while idioblasts occur more frequently in tubers. Interviews indicate that A. variabilis is rarely cultivated, although its glucomannan-rich tubers have strong potential for functional food and health products. These findings highlight the importance of functional anatomy for conservation planning. In situ conservation and community-based ex situ cultivation can support sustainable management while creating utilization opportunities that enhance local livelihoods.